The prey attack behavior of achaearanea tesselata (araneae, theridiidae) - Barrantes Montero, Gilbert (2006)
The attack behavior of the cobweb spider Achaearanea tesselata (Keyserling 1884) is roughly separated into three sequential steps: descend from the suspended retreat, pass through the sheet threads, and wrap the prey from underneath the sheet. The position and speed as the spider descended varied apparently according to prey type. In the fastest descent, A. tesselata fell free upside down, with all legs free and stretched upward. Two other relatively slow types of descent occurred when spiders approached the sheet head down or climbing down on a mesh thread. The behavior used to pass between the sheet lines showed little variation. It occurred at high speed with the legs folded dorsally; when the legs were in this position the spider offered a very small area of impact, apparently permitting the femora to penetrate or open a space between the lines of the sheet. The spider then opened the femora of the legs to create enough space for the cephalothorax, and seizing the sheet from underneath with legs I, II, and III, the spider pulled the abdomen and hind legs through the sheet. Then the spider rushed to the prey, flung viscid lines at the prey, and wrapped it. Attacks occurred in as little as 0.11 s after the spider began its descent. The design of the webs of A. tesselata transmits information regarding the location of the prey trapped on the sheet to reach the resting spider inside the retreat. The first response of the spider in her retreat was to turn to face the prey; the spider then climbed down along mesh threads following a nearly straight line to the prey.